THE EFFECT OF ORGANIZATIONAL CLIMATE, LEADERSHIP AND PROCEDURAL JUSTICE ON JOB SATISFACTION AT THE DEPARTMENT OF ENERGY AND MINERAL RESOURCES OF WEST SUMATRA - Yulihardi Yulihardi; Darman Darman; Yefri Reswita; Rina Febriani; Fransiska Julianti (PENANOMICS: International Journal of Economics, 2022)
Human resources are one of the important factors that cannot even be separated from an organization or company. Human resources are also the key that determines the development of an organization and acts as a mover, thinker and planner to achieve the goals of the organization, so the company must pay attention to the job satisfaction of all its employees. The purpose of this study was to determine how the influence of organizational climate, leadership and procedural justice on job satisfaction at the Department of Energy and Mineral Resources of West Sumatra.The type of research used in this research is associative research. The population in this study were all employees of the Department of Energy and Mineral Resources of West Sumatra as many as 72 people. The technique of collecting research data is through a questionnaire using a Likert scale. The data analysis technique in this research is multiple linear regression.Based on partial statistical analysis of organizational climate variables obtained t count 3.725 > t table 1.667 and a significant value (0.00 < 0.05) meaning H1 is accepted and Ho is rejected, it can be concluded that organizational climate has a positive and significant effect on job satisfaction at the Office Energy and Mineral Resources of West Sumatra. Leadership variable with a t value of 2.139 > 1.667 and a significant value (0.036 < 0.05) meaning H2 is accepted and Ho is rejected, it can be concluded that leadership has a positive and significant effect on job satisfaction at the Department of Energy and Mineral Resources of West Sumatra. The procedural justice variable with a calculated value of 2.685 > 1.667 and a significant value (0.009 < 0.05) means that H3 is accepted and Ho is rejected, it can be concluded that procedural justice has a positive and significant effect on job satisfaction at the Department of Energy and Mineral Resources of West Sumatra.The results of the F test are known that the calculated f value is 15.056 > f table 2.740 with a significant value of (0.000 <0.05), meaning that H4 accepts and Ho is rejected. It can be concluded that organizational climate, leadership and procedural justice simultaneously have a positive and significant effect on job satisfaction.